DIFFERENTIATED LEARNING WITHIN THE FRAMEWORK OF THE MERDEKA CURRICULUM AT THE ELEMENTARY SCHOOL LEVEL - Septiani, Windy; Bahri, Samsul; Winata, Nana Triana (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2025)
This research is a case study that employs a descriptive qualitative method. Data collection techniques involved interviews with one elementary school teacher and one Islamic elementary school teacher in Indramayu Regency. The Merdeka Curriculum is closely related to differentiated learning, as it serves as a framework that outlines the content to be taught and the instructional approaches utilized in an educational program. Differentiated learning approaches are integral to schools that implement the independent curriculum. This research was motivated by findings that some teachers lack an understanding of diagnostic assessment and differentiated learning approaches. Given the integral role of differentiated learning in the Merdeka Curriculum, this research aims to contribute to the development of more effective and efficient teaching practices. Based on these findings, the research elaborates on diagnostic assessment and differentiated learning concepts to enhance teachers’ comprehension of these essential elements. Consequently, it is expected that teachers will be able to implement differentiated learning more effectively and efficiently in the teaching process. Furthermore, this research aspires to enhance the quality of education and achieve better educational outcomes. Additionally, the research is a reference for future research on differentiated learning and diagnostic assessment, fostering teachers’ ability to implement more effective and efficient instructional strategies.